Porter’s Five Forces and Competitive Advantage : A Study on Banana Chips MSMEs in Bandar Lampung - Annisa Salsabila; Ribhan Ribhan (Green Inflation: International Journal of Management and Strategic Business Leadership, 2025)
Porter’s Five Forces, which include Supplier Bargaining Power, Threat of New Entrants, Intensity of Competitive Rivalry, and Buyer Bargaining Power, are crucial factors that companies must consider, as they can have a significant and negative impact on business operations. This approach enables companies to understand and map their strategic position within the industry. By analyzing these forces, MSMEs can identify external factors that either hinder or support their competitiveness. This study employs a quantitative descriptive research method using a survey in the form of a questionnaire. The population in this research consists of 183 individuals, including business owners and employees working at Banana Chips MSMEs in Bandar Lampung. The findings, which examine the influence of Porter’s Five Forces strategy on competitive advantage, indicate that implementing this strategy significantly enhances the competitiveness of Banana Chips MSMEs in Bandar Lampung. Porter’s Five Forces strategy, encompassing industry competition analysis, the threat of new entrants, supplier bargaining power, buyer bargaining power, and the threat of substitute products or services, serves as an essential tool for understanding a company’s position in a competitive market. By applying this strategy, Banana Chips MSMEs in Bandar Lampung can identify market opportunities and challenges, enabling them to develop effective strategic measures to maintain their competitive advantage over rivals. Therefore, Porter’s Five Forces strategy has proven to be highly relevant in fostering competitive advantage within the MSME sector.